Anomalous transport of a tracer on percolating clusters - Spanner, Markus; Hoefling, Felix; Schröder-Turk, Gerd; Mecke, Klaus; Franosch, Thomas (Journal of Physics: Condensed Matter, 2011)
We investigate the dynamics of a single tracer exploring a course of fixed obstacles in the vicinity of the percolation transition for particles confined to the infinite cluster. The mean-square displacement displays anomalous transport, which extends to infinite times precisely at the critical obstacle density. The slowing down of the diffusion coefficient exhibits power-law behavior for densities close to the critical point and we show that the mean-square displacement fulfills a scaling hypothesis. Furthermore, we calculate the dynamic conductivity as a response to an alternating electric field. Last, we discuss the non-Gaussian parameter as an indicator for heterogeneous dynamics.

Fluids in Extreme Confinement - Franosch, Thomas; Lang, Simon; Schilling, Rolf (Physical Review Letters, 2012)
For extremely confined fluids with a two-dimensional density n in slit geometry of an accessible width L, we prove that in the limit Li̊ghtarrow0, the lateral and transversal degrees of freedom decouple, and the latter become ideal-gas-like. For a small wall separation, the transverse degrees of freedom can be integrated out and renormalize the interaction potential. We identify nL2 as the hidden smallness parameter of the confinement problem and evaluate the effective two-body potential analytically, which allows calculating the leading correction to the free energy exactly. Explicitly, we map a fluid of hard spheres in extreme confinement onto a 2D fluid of disks with an effective hard-core diameter and a soft boundary layer. Two-dimensional phase transitions are robust and the transition point experiences a shift O(nL2).
EAM Import::2019-03-14

Mode-coupling theory of the glass transition for confined fluids - Lang, Simon; Schilling, Rolf; Krakoviack, Vincent; Franosch, Thomas (Physical Review E, 2012)
We present a detailed derivation of a microscopic theory for the glass transition of a liquid enclosed between two parallel walls relying on a mode-coupling approximation. This geometry lacks translational invariance perpendicular to the walls, which implies that the density profile and the density-density correlation function depends explicitly on the distances to the walls. We discuss the residual symmetry properties in slab geometry and introduce a symmetry adapted complete set of two-point correlation functions. Since the currents naturally split into components parallel and perpendicular to the walls the mathematical structure of the theory differs from the established mode-coupling equations in bulk. We prove that the equations for the nonergodicity parameters still display a covariance property similar to bulk liquids.
EAM Import::2019-03-12

Structural quantities of quasi-two-dimensional fluids - Lang, Simon; Franosch, Thomas; Schilling, Rolf (Journal of Chemical Physics, 2014)
Quasi-two-dimensional fluids can be generated by confining a fluid between two parallel walls with narrow separation. Such fluids exhibit an inhomogeneous structure perpendicular to the walls due to the loss of translational symmetry. Taking the transversal degrees of freedom as a perturbation to an appropriate 2D reference fluid we provide a systematic expansion of the m-particle density for arbitrary m. To leading order in the slit width this density factorizes into the densities of the transversal and lateral degrees of freedom. Explicit expressions for the next-to-leading order terms are elaborated analytically quantifying the onset of inhomogeneity. The case m = 1 yields the density profile with a curvature given by an integral over the pair-distribution function of the corresponding 2D reference fluid, which reduces to its 2D contact value in the case of pure excluded-volume interactions. Interestingly, we find that the 2D limit is subtle and requires stringent conditions on the fluid-wall interactions. We quantify the rapidity of convergence for various structural quantities to their 2D counterparts.
EAM Import::2019-03-13

Tagged-particle motion in a dense confined liquid - Lang, Simon; Franosch, Thomas (Physical Review E, 2014)
We investigate the dynamics of a tagged particle embedded in a strongly interacting confined liquid enclosed between two opposing flat walls. Using the Zwanzig-Mori projection operator formalism we obtain an equation of motion for the incoherent scattering function suitably generalized to account for the lack of translational symmetry. We close the equations of motion by a self-consistent mode-coupling ansatz. The interaction of the tracer with the surrounding liquid is encoded in generalized direct correlation functions. We extract the in-plane dynamics and provide a microscopic expression for the diffusion coefficient parallel to the walls. The solute particle may differ in size or interaction from the surrounding host-liquid constituents offering the possibility of a systematic analysis of dynamic effects on the tagged-particle motion in confinement.
EAM Import::2019-03-12